ANALYSIS OF THE IMPACT OF LIQUIDITY ON THE PROFITABILITY IN THE MEDIUM AND LARGE MEAT PROCESSING ENTERPRISES IN THE REPUBLIC OF SERBIA - Miroslav, Čavlin Sava; Vapa Tankosić, Jelena; Miletić, Vesna; Ivaniš, Miloš (Economics of Agriculture, 2021)
Liquidity and profitability are closely related economic categories. The issue of constant balancing between liquidity and profitability, in theory known as "liquidity profitability trade off", has been the subject of significant interest of the scientific community. There is no consensus on the direction of the impact of liquidity on profitability, but the existence of this impact in practice is confirmed. The aim of this paper is to investigate the impact of liquidity on profitability, based on selected traditional financial indicators, for medium and large enterprises in the group of processing and preserving of meat and meat products of the Republic of Serbia, in the period 2016 to 2019. The findings of a multiple linear regression analysis, show that the ratio of long-term sources and fixed assets in the group of processing and preserving of meat and meat products makes a statistically significant contribution predicting the return on assets.